Pulmonary capillary recruitment and distention in mammalian lungs: species similarities. (23rd February 2022) - Langleben, David; Fox, Benjamin D.; Orfanos, Stylianos E.; Giovinazzo, Michele; Catravas, John D.
Pulmonary arterial pressure rises minimally during exercise. The pulmonary microcirculation accommodates increasing blood flow via recruitment of pulmonary capillaries and, at higher flows, by distention of already perfused capillaries. The flow transition range between recruitment and distention has not been studied or compared across mammalian species, including humans. We hypothesised that the range would be similar. Functional pulmonary capillary surface area (FCSA) can be estimated using validated metabolic techniques. We reviewed data from previous studies in three mammalian species (perfused rabbit lungs and dog lung lobes, and exercising humans) and generated blood flow–FCSA curves over a range of flows. We noted where the curves diverged from the theoretical line of pure recruitment (Recruitment) and determined the flow where the curve slope equalled 50% that of Recruitment, or equalled that of a theoretical curve representing full capillary distention (Distention). The three mammalian species have similar flow ranges for the transition from predominantly recruitment to predominantly distention, with dogs having the highest transition point. Within the physiological range of most daily activity, the species are similar and accommodate increasing blood flow mainly via recruitment, with progressive distention at higher flows. This is highly relevant to pulmonary physiology during exercise. Lungs accept exercise blood flow by filling a larger fraction of their capillaries, then distending already filled capillaries as flow rises more. Our review shows the transition range is around 2.5 to 3.5 times resting flow in mammals, including humans. https://bit.ly/3JFWuG7